MONITORIZAREA CURRICULUMULUI ȘCOLAR LA DISCIPLINA LIMBA STRĂINĂ: CONCEPT, PARTICULARITĂȚI ȘI EXPERIENȚE - Guțu, Ion (Editura USM, 2024)
The national education system, since 1996, has as its basis its educational policies, along with the Education Code, an entire curricular system that regulates all the compartments intended for the pupils (conceptual framework, content components, teaching-learning-evaluation methodologies, guides implementation of curricula, etc.). Since the Curriculum is not a dogma, but a document in perpetual revision and modernization, it is necessary that the Curriculum in foreign languages of the latest generation (2018/2019) knows the continuous monitoring and development of all its compartments (concept, particularities, experiences) and at all cycles (primary and secondary) with the recommendation of a Methodological Framework to the ministry in order to prepare the next curricular generation. What are the challenges, what theories and methodologies can ensure the cyclical and continuous process of this curricular monitoring and development?
Keywords: education; curriculum development; foreign language